PENENTUAN MAHASISWA BERPRESTASI DENGAN METODE AHP DI STMIK PELITA NUSANTARA - Sadar Budi Wibowo; Murni Marbun (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2018)
Being an outstanding student has criteria according to the awarding institution. There are special requirements that must be met by the participants of outstanding student selection. The assessment component in STMIK Pelita Nusantara is the cumulative Achievement Index (GPA), scientific writing, superior performance / abilities, foreign language skills, and personality. Decision support systems (DSS) are part of computer-based information systems including knowledge-based systems or knowledge management that are used to support decision making in an organization or company. The determination of outstanding students includes unstructured problems because they have different criteria. With the Analytical Hierarchy Process (AHP) method, a criterion will be compared to other criteria in terms of how important it is to achieving goals with other criteria. The results of the assessment weight are two, namely achievement and not achieving. Of the 10 students who were categorized as achievers, after the application of the AHP calculation, Anas Prasetyo obtained it Value = 2.76 and Ari Kurniawan = 2.57. Students are in the category of Achievement.